Features of Chronology and Breeding Success of Pygoscelis papua and P. аdeliae (Spheniscidae) Penguins in the Wilhelm Archipelago (CCAMLR Subarea 48.1) - I. V. Dykyy; G. P. Milinevsky; O. L. Savitsky; D. G. Lutsenko; P. B. Khoetsky; M. F. Veselsky; V. M. Smagol; Ye. O. Dykyy; A. O. Dzhulay; J. V. Tsaryk; K. M. Nazaruk; A. T. Zatushevsky; et al. (Ukrainian Antarctic Journal, 2018)
Objective. To investigate the qualitative changes in the habitats of two most common species penguin populations in the Wilhelm Archipelago Pygoscelis papua and P. adeliae (Spheniscidae) penguins in the CCAMLR Subarea 48.1 under the impact of climate changes and krill fishery. Methods. The new method of time-lapse camera registration to observe the breeding success of penguins was applied to minimize the effect of human disturbance on the breeding and survival of chicks and to avoid disturbance of penguins. Installed in penguin colonies cameras were used to record next parameters: arrival to colony, copulation, egg lay, hatch and crèche. This method was introduced for the first time in the framework of the international CEMP project “Establishing a CEMP Camera Network in Subarea 48.1”. More than five years’ timeline of the project is expected. The traditional visual observation of penguin colonies from time to time has been used as well. Results. Over the last decade, P. papua has been shifted nearly 30 km southward and formed six new nesting colonies. Annual breeding success of P. papua on Petermann Island has ranged from 0.87 to 1.58 chicks crèche per nest over the nine seasonal observations during 2003—2017. 1.27 chicks per nest was found in 2016/17 season; a low breeding success rate in comparison to most of other seasons. The breeding success of P. adeliae was more stable ranging from 1.11 to 1.42 over the six seasonal observations; with highest in 2003/04. The range of prey for P. papua was studied. Conclusions. Changes in the penguin species habitat have been observed on the territory of the Wilhelm Archipelago. It was established that at the beginning of the ХХІ century the nesting areas of P. papua was significantly extended probably due to the climate warming in the region. It was shown that P. papua is more ecologically plastic species than P. adeliae. It is well know that the breeding success of predators such as penguins can be used as an indication of the status of lower trophic levels. Since, the Antarctic krill Euphausia superba (Euphausiidae) is the main feeding object of the both penguin species diet (84%) in the Wilhelm Archipelago area, we propose a model of key elements for qualitative and quantitative analysis of the changes in the krill- based ecosystem of the Argentine Islands. Future development of the penguin nesting colonies monitoring using the CEMP Camera Network under the CCAMLR will contribute significantly to the real-time estimates of relative prey availability. The results of the gentoo and Adelie penguin’s chronology and breeding success studies might be used (1) in development of the krill fishery management strategy in the CCAMLR for the rational use of Antarctic marine living resources; (2) to develop a resettlement model to predict the ecological risks due to climate changes for both penguin species.